2015
DOI: 10.1002/ange.201506593
|View full text |Cite
|
Sign up to set email alerts
|

Spontane Bildung von RNA‐Strängen, Peptidyl‐RNA und Cofaktoren

Abstract: Wie sich die heutige biochemische Maschinerie aus einfachen Vorläufern entwickelte, ist eine ungelöste Frage. Wir zeigen nun, dass Ribonukleotide und Aminosäuren in Abwesenheit von Enzymen zu Peptidyl‐RNAs kondensieren, und zwar unter Bedingungen, die auch spontanes genetisches Kopieren induzieren. Es treten templatfreie Bildung von RNA‐Strängen, die genetische Information codieren können, die Bildung von Peptidyl‐RNAs und die Bildung der Cofaktoren NAD+, FAD und ATP unter den gleichen Bedingungen auf. In den … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Further, it was found that the conditions described here unleash other intrinsic reactivities of nucleotides and amino acids,l eading to the spontaneous formation of peptidyl RNAs and cofactors,a sr eported in Ref. [33].…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…Further, it was found that the conditions described here unleash other intrinsic reactivities of nucleotides and amino acids,l eading to the spontaneous formation of peptidyl RNAs and cofactors,a sr eported in Ref. [33].…”
mentioning
confidence: 55%
“…Peaks for chains of up to at least nine AMP residues are discernable.T he formation of mixed sequences that can encode genetic information from any of the four ribonucleotides (A/C/G/U) is presented in Ref. [33].T aken together,o ur results confirm that "general condensation conditions" induce both high-yielding copying reactions and the untemplated de novo formation of RNA strands.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…We recently observed that amino acids and ribonucleotides condense into phosphoramidate‐linked species dubbed “peptido RNAs” when allowed to react in cold, homogeneous aqueous solution containing a condensing agent and an organocatalyst. [26] The formation of peptido RNA is a ribonucleotide‐promoted process, meaning that in the presence of a ribonucleotide component, peptide chain growth is faster than background oligomerization of the amino acid. [27] The phosphoramidate‐based pathway is not limited to reactions with water‐soluble carbodiimides, like EDC, as condensation agent.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we chanced upon an unexpected effect that we report upon here. Free peptides, rather than the nucleotide‐bound phosphoramidates expected,[ 26 , 29 ] were formed in macroscopic quantities from phenylalanine and tryptophan when a DNA or RNA assembly with a single‐ or double‐nucleotide gap in one of its helices was present at a micromolar concentration in a condensation buffer containing EDC. [26] This unencoded form of accelerated peptide formation is probably unrelated to translation, but may have provided a valuable biomaterial in prebiotic settings.…”
Section: Introductionmentioning
confidence: 99%